KAJIAN PENGGUNAAN DAN EFEK SAMPING RISPERIDONE DI RUMAH SAKIT JIWA GRHASIA YOGYAKARTA - Bangunawati Rahajeng; Salma Khoirunnisa Akbar (CERATA Jurnal Ilmu Farmasi, 2023)
Risperidone is an atypical antipsychotic indicated for acute and chronic schizophrenia and mania. A study found that the use of risperidone as a therapy for acute schizophrenia was 25.32%. Side effects of risperidone include insomnia, anxiety, headache, and extrapyramidal symptoms. With the high use of risperidone and the many possible side effects, it is necessary to study the drug. This study aims to describe the use and side effects of risperidone at the Ghrasia Mental Hospital Yogyakarta. This research is non-experimental research using a descriptive design. Data were collected retrospectively from medical records of a patient who received risperidone prescriptions at the Grhasia Mental Hospital Yogyakarta January-December 2019. Sampling used the purposive sampling technique, and 360 samples were obtained. The incidence of side effects was analyzed using the Naranjo algorithm. The use of risperidone at the Ghrasia Mental Hospital Yogyakarta showed that patients improved 25.83%, patients improved but had to control 71.17%. The incidence of side effects was 15% of the total 360 patients taking risperidone. The most common side effects were tremor (4.72%), insomnia 2.50%, nausea 1.67%, and vomiting 1.39%. Side effects were treated with 65% additional therapy, 22% no additional therapy, and 13% drug discontinuation. Conclusion: The use of risperidone at Ghrasia Hospital Yogyakarta shows good effectiveness with a 15% incidence of side effects that are handled properly